Ability of Kaoline Clays in Adsorption of Aniline,P-Nitro Aniline and 0-Toludine - Isha, S.A..; BaÂ·ssan, S.A.; Jahsim, K. G. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Adsorption   of   AniLine  and   some   derivatives  from   aqueous. solution  on kaolin  clays surface  was investigated, The isotherms  were of type  S3  d S4  according to Giles Classification.The   effect   of   introducing  electron   withdrawing  groups   andelectron  donatingGroups   in  the  aromatic  ring  on  the  adsorption  process   has   been investigated   ;  The  results showed  that the  extent  of  adsorption has been increased as aÂ·result  of substitution of groups, and found  that thederivatives  were   less   rn  adsorption    capacity   than   the   adsorptioncapacity  for the uil substituted compound.The  effect of the type of thsubstituted, grqup at the same sjte on the adsorption extent of aniline :was found  to decrease in the following order:Aniline  > o- nitro Aniline   >  a-ToluidineAdsorption on  kaolin  surface was examined  as afunction of temperature in the  range  (298-328k)  .  The  extent of adsorption  wasfound  to illc(ease with the increase in    temperature (Endothermic)Adsorption studies  nn  kaolin  clays surface  at different pH values. showed  an increase  in the  fol10wing order  according to  the  pH  of solution  for aniline and  o- tolu.       idine :pH       4  >11  >  7while foro-nitro Aniline showed  increase  in the fo-llo\ving order:pH       11 > 4  > 7